EVALUATING POWER METER APPLICATIONS FOR DYNAMIC ELECTRICITY EXPERIMENTS IN MIDDLE SCHOOL SCIENCE LABS - Diana Maulidia; Eka Cahya Prima (JURNAL PENA SAINS, 2026)
Integrating power meters into the science curriculum can significantly enhance students' understanding of technology and energy usage. Comprehending electricity enables pupils to grasp the operation of these gadgets, fostering practical knowledge and abilities. Teachers can assist students in understanding the financial and environmental consequences of their energy consumption patterns by including them in activities that encourage scientific investigation into the use of electronic devices at home. With more knowledge comes the possibility to make more thoughtful decisions about how much power to use, which might result in increased energy efficiency and financial savings. This is particularly important when it comes to electrical equipment, since improper use habits and increased energy expenses can arise from a lack of technology literacy. This research paper explores the implementation of Taffware Power Meters in the IPSE UPI laboratory to provide students with hands-on experience in measuring and analyzing energy consumption.  The study involves using various LED lamps with different wattages to demonstrate the practical applications of power meters in the classroom. Experimental findings have revealed a direct proportionality between electrical energy and time, while the measured power values of lamps closely match their rated specifications, except when the lamp power exceeds 8 watts, where discrepancies are observed.